The complete mitochondrial genome of the grass emperor, Lethrinus laticaudis (Perciformes: Lethrinidae). Issue 1 (1st January 2016) - Taillebois, Laura; Crook, David A.; Saunders, Thor; Williams, Samuel M.; Ovenden, Jennifer R.
Abstract: The grass emperor Lethrinus laticaudis is a coral reef fish that has high value to fisheries and is vulnerable to overharvesting. The complete mitochondrial genome was assembled from approximately 5.5 million reads produced by Illumina MiSeq. The 16, 758 bp consisted of 13 protein-coding genes, 22 transfer RNA genes and two ribosomal RNA genes (12S and 16S). The genes and RNAs order and orientation on as well as the A + T base content (50.7%) was similar to what is found in other Teleosts. A phylogenetic tree with the most closely related species available in GenBank was built to validate L. laticaudis mitogenome.